The Co-Cultural Communication Approach of Female Players in Facing Toxic Communication Behavior in Mobile Legends Bang Bang - Muhammad Nuh Fikrih; Herna Herna (Green Publisher Indonesia, 2025)
The study examines toxic communication in Mobile Legends Bang Bang among female players using Mark Obe's co-cultural communication theory. Employing a qualitative approach using constructivis paradigm, including interviews with eight female players, the research identifies how these players encounter and address toxic behavior. The findings reveal that most participants use an assertive accommodation approach. They actively challenge and attempt to change the prevailing norms in the game by reprimanding and educating those who engage in toxic behavior. They also utilize reporting and blocking features to manage these interactions, demonstrating resilience and a commitment to fostering a fairer gaming environment. Other participants adopt a non-assertive separation strategy. They avoid or isolate themselves from toxic situations, preferring non-confrontational methods to minimize interaction with those displaying toxic behavior. A smaller group uses an aggressive assimilation approach. These players conceal their virtual identities to blend in with the dominant group, adapting to the toxic norms rather than challenging them. The study highlights the various strategies female players use to cope with issues like sexual harassment, racism, insults, and trolling. This behavior includes trashing such as sexual harassment, racism, insults, intimidation, gender discrimination, and trolling (contextually inappropriate threats). Insults like n**b, janc*k, bngs*t, and cewek gbl*k are examples of toxic communication in online games. It underscores their awareness of the causes of toxic behavior, such as poor gameplay or social media influence, and their diverse methods of responding, from active confrontation to avoidance and adaptation.